Elvis and the Colonel : an insider's look at the most legendary partnership in show business - McDonald, Greg; Terrill, Marshall (St. Martin's Press, 2023)
"A fresh biography of legendary entertainment manager Colonel Tom Parker, with a contrarian and corrective point of view"--